Transfiguring Mindanao a Mindanao reader - Canuday, Jose Jowel; Sescon, Jose T. (Ateneo de Manila University Press, 2022)
This book has 34 chapters with 44 authors mostly coming from Mindanao covering broad topics from history, social, economic, political, and cultural features of the island and its people.--From the publisher.